1999
DOI: 10.1385/endo:11:1:61
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Abnormalities in Male Rats After Lactational Exposure to Nonylphenols

Abstract: Lactational exposure of male rat pups to nonylphenols (NPs) decreased the size of their testes and male accessory glands. At 31 d of age, NP-treatment of male rats resulted in less cellular differentiation of the seminiferous tubules (STs) and increased intertubular space compared to controls. At maturity, NP-treated males showed varying degrees of abnormalities in the affected testes. In the moderately affected ones, about 20-30% of their STs had poorly differentiated germinal elements. Cell lineage was less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
1
21
2
Order By: Relevance
“…In this paper, the level of NP in the animal body was not estimated, however the effects observed at 5 weeks might be partly dependent on this phenomenon. Several authors have observed that NP causes testicular abnormalities such as a lack of differentiation of seminiferous tubules and decreased sperm count and motility [37][38][39]. In the present study, the diminished sperm count after treatment with NP did not correlate with decreased testes weights.…”
Section: Discussioncontrasting
confidence: 53%
“…In this paper, the level of NP in the animal body was not estimated, however the effects observed at 5 weeks might be partly dependent on this phenomenon. Several authors have observed that NP causes testicular abnormalities such as a lack of differentiation of seminiferous tubules and decreased sperm count and motility [37][38][39]. In the present study, the diminished sperm count after treatment with NP did not correlate with decreased testes weights.…”
Section: Discussioncontrasting
confidence: 53%
“…NP could induce oxidative stress, cytotoxicity and apoptosis through endoplasmic reticulum stress in testicular sertoli cell in rat. Exposure of NP to neonatal rat has adverse effects with various reproductive parameters including decrease in the size of testis, reduced sperm count and sperm motility (Lee et al, 1999). In our experiments, NP 30 μM significantly decreased percentages of most boar sperm characteristics such as motility, viability, membrane integrity and mitochondrial activity for each 3, 6 or 9 hr incubation period (p<0.05).…”
Section: Discussionsupporting
confidence: 46%
“…In our experiments, NP 30 μM significantly decreased percentages of most boar sperm characteristics such as motility, viability, membrane integrity and mitochondrial activity for each 3, 6 or 9 hr incubation period (p<0.05). These results indicate that NP as endocrine disruptor also has direct detrimental effect on sperm characteristics despite of indirect effect mediated through the testicular tissue degeneration (Lee et al, 1999;El-Dakdoky and Helal, 2007). Addition of 10, 50 or 100 μM of DBP decreased overall boar sperm characteristics with dosedependency for 3, 6 or 9 hr incubation period (p<0.05).…”
Section: Discussionmentioning
confidence: 79%
“…Exposure to nonylphenol decreases the diameter of seminiferous tubule, lumen and epithelial thickness leading to testicular atrophy and cryptorchidism (de Jager et al 1999a). Gestational, lactational or direct exposure to nonylphenol has been shown to decrease testicular and epididymal masses (de Jager et al 1999b;Lee et al 1999). Nonylphenol produced a reduction in the activity of 17a-hydroxylase/C 17,20 -lyase in testicular homogenates of neonatal, pubertal and adult rats (Laurenzana et al 2002).…”
Section: Introductionmentioning
confidence: 99%